Heat-sealing cover tape capable of preventing self-adhesion and preparation method of heat-sealing cover tape

By constructing a microcapsule powder wrapped with hydrazide compound and forming a composite adhesive coating liquid, the problem of self-adhesion of the cover tape during the heat sealing process is solved, and the anti-self-adhesion and good adhesion properties after high-temperature heat sealing are achieved in a low-temperature environment.

CN119529702APending Publication Date: 2025-02-28GUIXI RUOBANG ELECTRONICS SCI & TECH

Patent Information

Application Number
CN202411822933.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the heat sealing process, the existing cover tapes are self-adhesive due to the adhesive coating itself, which affects the sealing effect.

Method used

By constructing a high-temperature fractureable microcapsule powder wrapped with hydrazide compounds, combining acrylate monomers, ketone compounds and azo initiators to form a composite adhesive coating liquid, applied to the surface of the pretreated polyethylene film, polymerized and cured to form a heat-sealing tape that is anti-self-adhesive.

Benefits of technology

Prevent self-adhesion in low temperature environments. After high-temperature heat sealing, the microcapsules rupture and release hydrazide compounds, and achieve good adhesion performance through ketohydrazine cross-linking, and improve the sealing effect of the heat sealing tape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-self-adhesion heat-sealing cover tape and a preparation method thereof, and belongs to the technical field of preparation of cover tapes for electronic components. The preparation method comprises the following steps: coating the surface of a pretreated polyethylene film with a composite adhesive coating solution, heating to 60-70 DEG C in an inert gas environment, reacting for 5-6 hours, and drying and curing to obtain the self-adhesion-preventing heat-sealing cover tape. The preparation method comprises the following steps: constructing microcapsule powder which is wrapped with a hydrazide compound and can be broken at high temperature, mixing the microcapsule powder, an acrylate monomer, a keto compound and an azo initiator to form a composite bonding coating liquid, smearing the surface of a pretreated polyethylene film with the composite bonding coating liquid, and then polymerizing and curing to form the self-adhesion-preventing heat-sealing cover tape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of cover tapes for electronic components, and in particular relates to a heat-sealed cover tape capable of preventing self-adhesion and a preparation method thereof. Background Art

[0002] With the rapid development of modern electronic technology, the packaging technology of electronic components has also been constantly evolving and innovating. As an important component of electronic component packaging, cover tape plays a vital role in ensuring the performance of electronic components, improving product reliability and extending service life. The functions of cover tape include: (1) It can effectively block external physical and chemical damage, protect internal electronic components from dust, moisture, chemicals, etc., thereby extending the service life of the product; (2) It has good electrical insulation performance, can prevent problems such as short circuits and leakage, and ensure the normal operation of electronic components; (3) Certain types of cover tape have excellent thermal conductivity, which helps electronic components dissipate heat during operation and prevent performance degradation or failure due to overheating; (4) It not only provides protection, but also can enhance the appearance of the product through printing, color, etc. Many cover tapes are also printed with information such as product name, model, and production date, which serves as an identification function; (5) In the packaging of sensitive electronic components, antistatic cover tape can effectively prevent static electricity from damaging components, ensuring the safety and stability of electronic products; (6) Modern cover tape design usually takes into account the convenience of processing and assembly, and can be used in conjunction with automated equipment to improve production efficiency and reduce labor costs.

[0003] Patent CN113426643A discloses a multi-layer heat-sealing cover tape and a preparation method thereof, wherein the heat-sealing cover tape of the invention comprises a substrate film layer, a first antistatic layer is arranged below the substrate film layer, a water-gel layer is arranged above the substrate film layer, a buffer layer is arranged above the water-gel layer, a heat-sealing layer is arranged above the buffer layer, and a second antistatic layer is arranged above the heat-sealing layer. By arranging the water-gel layer between the substrate film layer and the buffer layer, the heat-sealing cover tape can maintain dimensional stability after alternating between hot and cold in an oven, and will not shrink or deform, thereby making the heat-sealing cover tape smooth in appearance, and having stable peeling force after sealing. After sealing and packaging, the electronic components inside will not be displaced due to the extra gaps caused by the outward protrusion of the heat-sealing cover tape, causing adverse effects.

[0004] Patent CN115027115A discloses an environmentally friendly composite cover tape and its preparation process. The cover tape of the invention has a structure of PET layer, PE layer and TPE layer from top to bottom. The strength of the PE layer is increased by a reasonable ratio of polyethylene and plasticizer; SEBS modified by maleic anhydride effectively improves the thermal stability of the cover tape, and also improves the bonding strength and strength between the film layers; by controlling the weight ratio of ethylene / sodium methacrylate copolymer, the stability and bonding force of the interface between the cover tape film layers are effectively improved, while the toughness of the TPE layer is improved and the antistatic properties and antistatic stability of the film are improved.

[0005] The above invention has achieved good improvement on the heat-sealing stability and antistatic performance of the cover tape. However, in actual use, the coating on the cover tape that plays an adhesive role is easy to stick to itself during the bonding process with the carrier tape due to its own viscosity, which leads to the failure of the carrier tape sealing. For this reason, the anti-self-adhesion property of the cover tape has been modified in the prior art.

[0006] Patent CN112500753A discloses an anti-adhesive, anti-static heat-sealing coating and cover tape. The invention uses cellulose acetate butyrate as an anti-adhesive agent and controls the Tg of the coating liquid at 60-80°C to ensure that the heat-sealing coating has a good anti-adhesive effect.

[0007] During the process of heat sealing the carrier tape, the temperature is relatively high. By utilizing the property of breaking in response to temperature, a heat-sealing cover tape is prepared that has no adhesion effect at low temperatures but achieves adhesion effect through temperature response at high temperatures. This is of great significance for improving the anti-self-adhesion effect of the heat-sealing cover tape. Summary of the invention

[0008] In view of the deficiencies of the prior art, the present invention solves the technical problems raised in the background technology by constructing a high-temperature breakable microcapsule powder wrapped with a hydrazide compound, applying a composite adhesive coating liquid formed by mixing the microcapsule powder, an acrylate monomer, a ketone compound and an azo initiator on the surface of a pretreated polyethylene film, and then polymerizing and curing to form an anti-self-adhesive heat-sealing cover tape. Specifically, the technical solution of the present invention includes the following contents: A method for preparing a heat-sealing cover tape capable of preventing self-adhesion, the method comprising the following steps: The composite adhesive coating liquid is applied to the surface of the pretreated polyethylene film and heated to 60° C. to 70° C. in an inert gas environment for reaction for 5 h to 6 h, and then dried and solidified to obtain the anti-self-adhesive heat-sealing cover tape.

[0009] Furthermore, the preparation method of the composite adhesive coating liquid comprises the following steps: The conjugated diene alcohol and the diene derivative are mixed in a molar ratio of 1:3-4, heated to 50°C-60°C and reacted for 24h-30h to obtain a DA type diol monomer; The DA type diol monomer, hydrazide compound, deionized water and surfactant are mixed and stirred in a mass ratio of 1:1:20-30:0.01-0.02 to obtain an aqueous phase; The aqueous phase and the aliphatic diisocyanate are mixed and emulsified in a mass ratio of 7-8:2-3 to obtain a mixed emulsion; The mixed emulsion is mixed with an organic tin catalyst and heated to 70° C. to 80° C. for reaction for 1.5 h to 2 h, and then an enol capping agent is added, mixed, and heated to 85° C. to 90° C. for reaction for 3 h to 4 h to obtain microcapsule powder; The microcapsule powder, acrylate monomer, keto compound containing carbon-carbon double bond, organic solvent and azo initiator are mixed and stirred in a mass ratio of 1-2:2-5:0.5-1:8-15:0.05-0.08 to obtain the composite adhesive coating liquid.

[0010] Furthermore, the conjugated diene alcohol is furfuryl alcohol.

[0011] Furthermore, the diene derivative includes N,N'-(4,4'-methylenediphenyl)bismaleimide, and the two carbon-carbon double bond structures on the diene derivative are used to introduce a DA-type diol monomer having two hydroxyl structures. The DA-type diol monomer having two hydroxyl structures can be polymerized and extended with aliphatic diisocyanate through the two hydroxyl structures.

[0012] Furthermore, the hydrazide compound includes nicotinic acid hydrazide or benzoyl hydrazide, and the hydrazide compound needs to contain a rigid planar benzene ring or pyridine ring structure to improve the mechanical properties of the adhesive back cover tape.

[0013] Furthermore, the surfactant includes cocamidopropyl betaine, 3-sulfopropyl tetradecyl dimethyl betaine or lauryl betaine.

[0014] Furthermore, the aliphatic diisocyanate includes hexamethylene diisocyanate, isophorone diisocyanate or dicyclohexylmethane-4,4'-diisocyanate.

[0015] Furthermore, the mixed emulsification conditions include an emulsification speed of 5000 r / min to 8000 r / min and an emulsification time of 4 min to 8 min.

[0016] Furthermore, the organic tin catalyst includes dibutyltin dilaurate.

[0017] Furthermore, the enol capping agent includes dihydromyrcenol, and the enol capping agent must have a carbon-carbon double bond for participating in the polymerization reaction, and then can be introduced into the heat-sealing cover tape through the polymerization reaction on the surface of the pretreated polyethylene film.

[0018] Furthermore, the mass ratio of the mixed emulsion, the organic tin catalyst and the enol capping agent is 1:0.0005-0.001:0.4-0.5.

[0019] Furthermore, the acrylate monomer includes methyl methacrylate or ethyl methacrylate, and the acrylate monomer is used to adjust the flexibility of the polymer to prevent excessive rigidity from causing the heat-sealing cover tape to break and crack, thereby losing its sealing function.

[0020] Furthermore, the keto compound containing a carbon-carbon double bond includes N,N'-methylenebisacrylamide or diacetone acrylamide. The carbon-carbon double bond of the keto compound containing a carbon-carbon double bond can also be introduced into the heat-sealing cover tape by participating in a polymerization reaction. During subsequent high-temperature heat sealing, ketohydrazine cross-linking can occur to achieve adhesion.

[0021] Furthermore, the organic solvent is obtained by mixing equal amounts of ethanol and acetone.

[0022] Furthermore, the azo initiator includes azobisisobutyronitrile, azobisisovaleronitrile or azobisisoheptanenitrile.

[0023] Furthermore, the composite adhesive coating liquid may be applied to the surface of the pretreated polyethylene film by intermittent coating, or other coating methods may be used according to actual needs.

[0024] Furthermore, the method for preparing the pretreated polyethylene film comprises the following steps: The polyethylene film is treated under irradiation conditions of 100 Gy / h to 110 Gy / h radiation dose rate and 50 kGy to 90 kGy radiation dose to obtain the pretreated polyethylene film.

[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention constructs a DA-type diol monomer with a cyclohexene structure that can undergo addition reaction at a relatively low temperature and can break under a high temperature environment through a DA reaction, and then the hydroxyl structure on the DA-type diol monomer can undergo polymerization reaction with isocyanate, and diisocyanate is used as a capsule wall material, and a hydrazide compound that can cross-link with a ketone group to improve adhesion is used as a core material, and the water phase and the oil phase aliphatic diisocyanate that encapsulate the DA-type diol monomer and the hydrazide compound are interfacially polymerized in the constructed emulsion system, and then dihydromyrcenol containing a single hydroxyl structure and a single carbon-carbon double bond structure is used as an enol capping agent, and under the action of a catalyst, a microcapsule powder encapsulated with the hydrazide compound is finally obtained. Then, the microcapsule powder, an acrylate monomer, a ketone compound that can cross-link with the hydrazide compound to improve adhesion and has a carbon-carbon double bond, and an azo initiator are mixed to form a composite adhesive coating liquid. The composite adhesive coating liquid is applied to the surface of the pretreated polyethylene film with a free radical structure obtained by irradiation treatment, and then the composite adhesive coating liquid is solidified on the pretreated polyethylene film through a free radical polymerization reaction, and the composite adhesive coating liquid and the pretreated polyethylene film form an anti-self-adhesive heat-sealing cover tape. The anti-self-adhesive heat-sealing cover tape cannot release hydrazide compounds in a low-temperature environment and exhibits a non-adhesive property; when heat-sealed at a high temperature, the cyclohexene structure constructed by the DA reaction can be broken, thereby causing the microcapsule structure constructed by the DA-type diol monomer to rupture, releasing the core material hydrazide compound inside the microcapsule, and the released hydrazide compound can be cross-linked with the ketone group through the hydrazide group structure, thereby achieving adhesion performance, thereby improving the self-adhesive phenomenon of the adhesive layer of the heat-sealing cover tape.

[0026] (2) The present invention uses the synergistic combination of a hydrazide compound having a rigid planar structure and an acrylate monomer having a rotatable single bond and capable of adjusting the flexibility of the polymer, so that the anti-self-adhesive heat-sealing cover tape prepared by the present invention has good toughness, reduces the risk of the cover tape breaking and falling off due to excessive rigidity after heat-sealing and peeling, and has a good promoting effect on extending the service life of the cover tape. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0029] Preparation Example 1: The preparation of the composite adhesive coating liquid specifically includes the following processes: Weigh 0.1 mol of N,N'-(4,4'-methylenediphenyl)bismaleimide and 0.3 mol of furfuryl alcohol and add them to 300 mL of N,N-dimethylformamide solution and stir until completely dissolved. Then control the stirring speed to 100 r / min, heat to 50 °C and stir to react for 24 hours. After the reaction is completed, remove N,N-dimethylformamide by evaporation under reduced pressure to obtain DA type diol monomer.

[0030] 30 g of DA type diol monomer, 30 g of nicotinic acid hydrazide, 600 g of deionized water and 0.3 g of cocamidopropyl betaine were weighed and mixed to obtain an aqueous phase. 100 g of hexamethylene diisocyanate and 350 g of the aqueous phase were weighed and mixed and put into a homogenizer, and emulsified at a speed of 5000 r / min for 4 min to obtain a mixed emulsion.

[0031] Pour the mixed emulsion into a beaker, and then heat it to 70°C in a water bath, then immediately add 0.225g of dibutyltin dilaurate, and continue stirring and reacting for 1.5h at a stirring speed of 100r / min. After the reaction is completed, add 180g of dihydromyrcenol, mix and stir, and further heat to 85°C for end-capping reaction for 3h to obtain a microcapsule suspension. The microcapsule suspension is centrifuged, washed with petroleum ether, and then placed in a drying oven at 70°C for drying to obtain microcapsule powder.

[0032] 200 g of microcapsule powder, 400 g of methyl methacrylate, 100 g of N,N'-methylenebisacrylamide, 1600 g of organic solvent (mixed from 800 g of ethanol and 800 g of acetone) and 10 g of azobisisobutyronitrile were mixed and stirred until uniformly dispersed to obtain a composite adhesive coating liquid.

[0033] Preparation Example 2: The preparation of the composite adhesive coating liquid specifically includes the following processes: Weigh 0.1 mol of N,N'-(4,4'-methylenediphenyl)bismaleimide and 0.32 mol of furfuryl alcohol and add them to 300 mL of N,N-dimethylformamide solution and stir until completely dissolved. Then control the stirring speed to 100 r / min, heat to 52 °C and stir for 24 hours. After the reaction is completed, remove N,N-dimethylformamide by evaporation under reduced pressure to obtain DA type diol monomer.

[0034] 30 g of DA type diol monomer, 30 g of nicotinic acid hydrazide, 650 g of deionized water and 0.4 g of cocamidopropyl betaine were weighed and mixed to obtain an aqueous phase. 110 g of hexamethylene diisocyanate and 360 g of the aqueous phase were weighed and mixed and put into a homogenizer, and emulsified at a speed of 5000 r / min for 4 min to obtain a mixed emulsion.

[0035] Pour the mixed emulsion into a beaker, and then heat it to 72°C in a water bath, then immediately add 0.282g of dibutyltin dilaurate, and continue stirring and reacting for 1.5h at a stirring speed of 110r / min. After the reaction is completed, add 188g of dihydromyrcenol, mix and stir, and further heat to 85°C for end-capping reaction for 3h to obtain a microcapsule suspension. The microcapsule suspension is centrifuged, washed with petroleum ether, and then placed in a drying oven at 70°C for drying to obtain microcapsule powder.

[0036] 250 g of microcapsule powder, 500 g of methyl methacrylate, 120 g of N,N'-methylenebisacrylamide, 2000 g of organic solvent (mixed from 1000 g of ethanol and 1000 g of acetone) and 12 g of azobisisobutyronitrile were mixed and stirred until uniformly dispersed to obtain a composite adhesive coating liquid.

[0037] Preparation Example 3: The preparation of the composite adhesive coating liquid specifically includes the following processes: Weigh 0.1 mol of N,N'-(4,4'-methylenediphenyl)bismaleimide and 0.34 mol of furfuryl alcohol and add them to 300 mL of N,N-dimethylformamide solution and stir until completely dissolved. Then control the stirring speed to 150 r / min, heat to 55 °C and stir for 26 hours. After the reaction is completed, remove N,N-dimethylformamide by evaporation under reduced pressure to obtain DA type diol monomer.

[0038] 30 g of DA type diol monomer, 30 g of nicotinic acid hydrazide, 700 g of deionized water and 0.4 g of 3-sulfopropyl tetradecyl dimethyl betaine were weighed and mixed to obtain an aqueous phase. 120 g of isophorone diisocyanate and 370 g of the aqueous phase were weighed and mixed and put into a homogenizer, and emulsified at a speed of 6000 r / min for 5 min to obtain a mixed emulsion.

[0039] Pour the mixed emulsion into a beaker, and then heat it to 74°C in a water bath, then immediately add 0.343g of dibutyltin dilaurate, and continue stirring and reacting at a stirring speed of 120r / min for 1.5h. After the reaction is completed, add 220.5g of dihydromyrcenol, mix and stir, and further heat to 85°C for end-capping reaction for 3.5h to obtain a microcapsule suspension. The microcapsule suspension is centrifuged, washed with petroleum ether, and then placed in a drying oven at 70°C for drying to obtain microcapsule powder.

[0040] 300 g of microcapsule powder, 600 g of methyl methacrylate, 140 g of N,N'-methylenebisacrylamide, 2400 g of organic solvent (mixed from 1200 g of ethanol and 1200 g of acetone) and 12 g of azobisisovaleronitrile were mixed and stirred until uniformly dispersed to obtain a composite adhesive coating liquid.

[0041] Preparation Example 4: The preparation of the composite adhesive coating liquid specifically includes the following processes: Weigh 0.1 mol of N,N'-(4,4'-methylenediphenyl)bismaleimide and 0.36 mol of furfuryl alcohol and add them to 300 mL of N,N-dimethylformamide solution and stir until completely dissolved. Then control the stirring speed to 150 r / min, heat to 57 °C and stir for 26 hours. After the reaction is completed, remove N,N-dimethylformamide by evaporation under reduced pressure to obtain DA type diol monomer.

[0042] 30 g of DA type diol monomer, 30 g of benzoyl hydrazide, 750 g of deionized water and 0.5 g of 3-sulfopropyl tetradecyl dimethyl betaine were weighed and mixed to obtain an aqueous phase. 130 g of isophorone diisocyanate and 380 g of the aqueous phase were weighed and mixed and put into a homogenizer, and emulsified at a speed of 6000 r / min for 6 minutes to obtain a mixed emulsion.

[0043] Pour the mixed emulsion into a beaker, and then heat it to 76°C in a water bath, then immediately add 0.408g of dibutyltin dilaurate, and continue stirring and reacting at a stirring speed of 130r / min for 2h. After the reaction is completed, add 229.5g of dihydromyrcenol, mix and stir, and further heat to 90°C for end-capping reaction for 3.5h to obtain a microcapsule suspension. The microcapsule suspension is centrifuged, washed with petroleum ether, and then placed in a drying oven at 70°C for drying to obtain microcapsule powder.

[0044] 350 g of microcapsule powder, 800 g of ethyl methacrylate, 160 g of diacetone acrylamide, 2600 g of an organic solvent (a mixture of 1300 g of ethanol and 1300 g of acetone) and 14 g of azobisisovaleronitrile were mixed and stirred until uniformly dispersed to obtain a composite adhesive coating liquid.

[0045] Preparation Example 5: The preparation of the composite adhesive coating liquid specifically includes the following processes: Weigh 0.1 mol of N,N'-(4,4'-methylenediphenyl)bismaleimide and 0.38 mol of furfuryl alcohol and add them to 300 mL of N,N-dimethylformamide solution and stir until completely dissolved. Then control the stirring speed to 200 r / min, heat to 60 °C and stir for 28 hours. After the reaction is completed, remove N,N-dimethylformamide by evaporation under reduced pressure to obtain DA type diol monomer.

[0046] 30 g of DA type diol monomer, 30 g of benzoyl hydrazide, 800 g of deionized water and 0.5 g of lauryl betaine were weighed and mixed to obtain an aqueous phase. 140 g of dicyclohexylmethane-4,4'-diisocyanate and 390 g of the aqueous phase were weighed and mixed and put into a homogenizer, and emulsified at a speed of 7000 r / min for 7 minutes to obtain a mixed emulsion.

[0047] Pour the mixed emulsion into a beaker, and then heat it to 78°C in a water bath, then immediately add 0.447g of dibutyltin dilaurate, and continue stirring at a stirring speed of 140r / min for 2h. After the reaction is completed, add 265g of dihydromyrcenol, mix and stir, and further heat to 90°C for 4h to obtain a microcapsule suspension. The microcapsule suspension is centrifuged, washed with petroleum ether, and then dried in a drying oven at 70°C to obtain microcapsule powder.

[0048] 400 g of microcapsule powder, 900 g of ethyl methacrylate, 180 g of diacetone acrylamide, 2800 g of an organic solvent (a mixture of 1400 g of ethanol and 1400 g of acetone) and 14 g of azobisisoheptonitrile were mixed and stirred until uniformly dispersed to obtain a composite adhesive coating liquid.

[0049] Preparation Example 6: The preparation of the composite adhesive coating liquid specifically includes the following processes: Weigh 0.1 mol of N,N'-(4,4'-methylenediphenyl)bismaleimide and 0.38 mol of furfuryl alcohol and add them to 300 mL of N,N-dimethylformamide solution and stir until completely dissolved. Then control the stirring speed to 200 r / min, heat to 60 °C and stir for 30 hours. After the reaction is completed, remove N,N-dimethylformamide by evaporation under reduced pressure to obtain DA type diol monomer.

[0050] 30 g of DA type diol monomer, 30 g of benzoyl hydrazide, 900 g of deionized water and 0.6 g of lauryl betaine were weighed and mixed to obtain an aqueous phase. 150 g of dicyclohexylmethane-4,4'-diisocyanate and 400 g of the aqueous phase were weighed and mixed and put into a homogenizer, and emulsified at a speed of 8000 r / min for 8 minutes to obtain a mixed emulsion.

[0051] Pour the mixed emulsion into a beaker, place it in a water bath and heat it to 80°C, then immediately add 0.55g of dibutyltin dilaurate, and continue stirring and reacting at a stirring speed of 150r / min for 2h. After the reaction is completed, add 275g of dihydromyrcenol, mix and stir, and further heat to 90°C for end-capping reaction for 4h to obtain a microcapsule suspension. The microcapsule suspension is centrifuged and washed with petroleum ether, and then placed in a drying oven at 70°C for drying to obtain microcapsule powder.

[0052] 400 g of microcapsule powder, 1000 g of ethyl methacrylate, 200 g of diacetone acrylamide, 3000 g of organic solvent (mixed from 1500 g of ethanol and 1500 g of acetone) and 16 g of azobisisoheptanenitrile were mixed and stirred until uniformly dispersed to obtain a composite adhesive coating liquid.

[0053] Preparation Example 7: The preparation of the composite adhesive coating liquid specifically includes the following processes: The N,N'-(4,4'-methylenediphenyl)bismaleimide in Preparation Example 6 was replaced with maleic anhydride, and the other conditions were kept consistent with Preparation Example 6.

[0054] Preparation Example 8: The preparation of the composite adhesive coating liquid specifically includes the following processes: The benzoyl hydrazide in Preparation Example 6 was replaced by salicyloyl hydrazide, and the other conditions were kept the same as those in Preparation Example 6.

[0055] Preparation Example 9: The preparation of the composite adhesive coating liquid specifically includes the following processes: The dicyclohexylmethane-4,4'-diisocyanate in Preparation Example 6 was replaced by toluene-2,4-diisocyanate, and the other conditions were kept the same as those in Preparation Example 6.

[0056] Preparation Example 10: The preparation of the composite adhesive coating liquid specifically includes the following processes: The ethyl methacrylate in Preparation Example 6 was removed and not added, and the other conditions remained the same as those in Preparation Example 6.

[0057] Preparation Example 11: The preparation of pretreated polyethylene film specifically includes the following processes: Place the polyethylene film in an ultrasonic cleaning machine, add isopropanol as the ultrasonic cleaning liquid to completely submerge the polyethylene film, then adjust the ultrasonic power to 200W, and perform ultrasonic cleaning for 20 minutes. After cleaning, remove the polyethylene film, replace the isopropanol with deionized water, and clean it again at 200W ultrasonic power for 20 minutes. After cleaning, remove the polyethylene film and purge the moisture on the surface with nitrogen, then place it in a drying oven at 50°C for 12 hours.

[0058] The dried polyethylene film was placed in an irradiation box, the air in the irradiation box was replaced with argon, and then the polyethylene film was irradiated in an argon atmosphere at a radiation dose rate of 100 Gy / h and a radiation dose of 50 kGy to obtain a pretreated polyethylene film.

[0059] Preparation Example 12: The preparation of pretreated polyethylene film specifically includes the following processes: Place the polyethylene film in an ultrasonic cleaning machine, add isopropanol as the ultrasonic cleaning liquid to completely submerge the polyethylene film, then adjust the ultrasonic power to 200W, and perform ultrasonic cleaning for 20 minutes. After cleaning, remove the polyethylene film, replace the isopropanol with deionized water, and clean it again at 200W ultrasonic power for 20 minutes. After cleaning, remove the polyethylene film and purge the moisture on the surface with nitrogen, then place it in a drying oven at 50°C for 12 hours.

[0060] The dried polyethylene film was placed in an irradiation box, the air in the irradiation box was replaced with argon, and then the polyethylene film was irradiated in an argon atmosphere at a radiation dose rate of 105 Gy / h and a radiation dose of 70 kGy to obtain a pretreated polyethylene film.

[0061] Preparation Example 13: The preparation of pretreated polyethylene film specifically includes the following processes: Place the polyethylene film in an ultrasonic cleaning machine, add isopropanol as the ultrasonic cleaning liquid to completely submerge the polyethylene film, then adjust the ultrasonic power to 200W, and perform ultrasonic cleaning for 20 minutes. After cleaning, remove the polyethylene film, replace the isopropanol with deionized water, and clean it again at 200W ultrasonic power for 20 minutes. After cleaning, remove the polyethylene film and purge the moisture on the surface with nitrogen, then place it in a drying oven at 50°C for 12 hours.

[0062] The dried polyethylene film was placed in an irradiation box, the air in the irradiation box was replaced with argon, and then the polyethylene film was irradiated in an argon atmosphere at a radiation dose rate of 110 Gy / h and a radiation dose of 90 kGy to obtain a pretreated polyethylene film.

[0063] Embodiment 1: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 1 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 11 and the temperature was raised to 60°C in an inert gas environment for polymerization reaction for 5 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0064] Embodiment 2: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 2 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 11 and the temperature was raised to 60°C in an inert gas environment for polymerization reaction for 5 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0065] Embodiment 3: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 3 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 12 and the film was heated to 65°C in an inert gas environment for polymerization reaction for 5 hours. After the reaction, the film was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0066] Embodiment 4: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 4 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 12 and the temperature was raised to 65°C for polymerization reaction for 6 hours under an inert gas environment. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0067] Embodiment 5: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 5 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 13 and the temperature was raised to 70°C in an inert gas environment for polymerization reaction for 6 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0068] Embodiment 6: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 6 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 13 and the film was heated to 70°C in an inert gas environment for polymerization for 6 hours. After the reaction, the film was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0069] Comparative Example 1: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 7 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 13 and the temperature was raised to 70°C in an inert gas environment for polymerization reaction for 6 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0070] Comparative Example 2: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 8 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 13 and the temperature was raised to 70°C in an inert gas environment for polymerization reaction for 6 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0071] Comparative Example 3: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 9 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 13 and the temperature was raised to 70°C in an inert gas environment for polymerization reaction for 6 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0072] Comparative Example 4: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 10 was applied to the surface of the pretreated polyethylene film obtained in Preparation Example 13 and the temperature was raised to 70°C in an inert gas environment for polymerization reaction for 6 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0073] Comparative Example 5: A preparation method of a heat-sealing cover tape capable of preventing self-adhesion includes the following steps: The composite adhesive coating liquid obtained in Preparation Example 6 was applied to the surface of the polyethylene film that had not been pretreated and heated to 70°C in an inert gas environment for polymerization reaction for 6 hours. After the reaction, it was placed in a blast drying oven at 55°C for drying for 24 hours, and then taken out and cooled to room temperature to obtain an anti-self-adhesive heat-sealing cover tape.

[0074] The anti-self-adhesive heat-sealing cover tapes prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were attached to the surface of the carrier tape, and then heat-sealed at 50° C., 100° C. and 150° C., respectively. After cooling to room temperature, the tapes were peeled off at a pulling speed of 300 mm / min and the peel strength (N / 15 mm) was recorded. The results are shown in the table below.

[0075] Through the above peel strength test results, it can be found that: (1) In Examples 1 to 6 of the present invention, a high-temperature breakable microcapsule powder encapsulated with a hydrazide compound is constructed. A composite adhesive coating liquid formed by mixing the microcapsule powder, an acrylate monomer, a keto compound and an azo initiator is applied to the surface of a pretreated polyethylene film, and then polymerized and cured to form a heat-sealing cover tape, which is easy to fall off in a low-temperature environment and has low viscosity. After high-temperature heat sealing, the hydrazide compound released by the rupture of the microcapsules undergoes ketohydrazine cross-linking with the keto compound, thereby achieving good adhesion performance.

[0076] (2) It can be seen from Comparative Example 1 that since maleic anhydride introduces a single hydroxyl group into the structure through a DA reaction, it is unable to introduce a dihydroxyl structure, resulting in the inability to polymerize and extend, and unable to form a wrap around the hydrazide compound. Ketohydrazine cross-linking can occur at a relatively low temperature, making the cover tape easy to self-adhere.

[0077] (3) It can be seen from Comparative Example 2 that although salicylic hydrazide can undergo ketohydrazide cross-linking with keto compounds to achieve adhesion, salicylic hydrazide contains hydroxyl groups in its structure and can participate in the polymerization reaction with diisocyanate, resulting in poor wrapping of the hydrazide compound. Ketohydrazide cross-linking can occur at a relatively low temperature, making the cover tape easy to self-adhere.

[0078] (4) It can be seen from Comparative Example 3 that although toluene-2,4-diisocyanate can be used as a polymerization substrate to achieve the encapsulation of hydrazide compounds for comparison, since toluene-2,4-diisocyanate contains a benzene ring in its structure, the introduction of the benzene ring further increases the rigidity of the cover tape, resulting in poor mechanical properties. When peeling off after high-temperature heat sealing, it is easy to break and crack, causing it to fall off, which is not conducive to the use of the cover tape.

[0079] (5) It can be seen from Comparative Example 4 that the carbon chain of ethyl methacrylate is easy to rotate and provides greater intermolecular freedom, preventing excessive rigidity from causing the heat-sealed cover tape to break and crack, thereby losing its sealing effect. If ethyl methacrylate and other acrylic acid ester monomers are not added to modify the toughness of the cover tape, it is easy to break and crack when peeled off after high-temperature heat sealing, causing it to fall off, which is not conducive to the use of the cover tape.

[0080] (6) It can be seen from Comparative Example 5 that there are no free radicals on the surface of the untreated polyethylene film. Relying solely on the catalytic effect of the azo initiator, the composite adhesive coating liquid is difficult to solidify on the polyethylene film, which results in a poor heat-sealing effect of the cover tape.

[0081] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion, characterized in that: The preparation method comprises the following steps: The composite adhesive coating liquid is applied to the surface of the pretreated polyethylene film and heated to 60° C. to 70° C. in an inert gas environment for reaction for 5 h to 6 h, and then dried and solidified to obtain the anti-self-adhesive heat-sealing cover tape.

2. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 1, characterized in that: The preparation method of the composite adhesive coating liquid comprises the following steps: The conjugated diene alcohol and the diene derivative are mixed in a molar ratio of 1:3-4, heated to 50°C-60°C and reacted for 24h-30h to obtain a DA type diol monomer; The DA type diol monomer, hydrazide compound, deionized water and surfactant are mixed and stirred in a mass ratio of 1:1:20-30:0.01-0.02 to obtain an aqueous phase; The aqueous phase and the aliphatic diisocyanate are mixed and emulsified in a mass ratio of 7-8:2-3 to obtain a mixed emulsion; The mixed emulsion is mixed with an organic tin catalyst and heated to 70° C. to 80° C. for reaction for 1.5 h to 2 h, and then an enol capping agent is added, mixed, and heated to 85° C. to 90° C. for reaction for 3 h to 4 h to obtain microcapsule powder; The microcapsule powder, acrylate monomer, keto compound containing carbon-carbon double bond, organic solvent and azo initiator are mixed and stirred in a mass ratio of 1-2:2-5:0.5-1:8-15:0.05-0.08 to obtain the composite adhesive coating liquid.

3. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 2, characterized in that: The conjugated diene alcohol is furfuryl alcohol.

4. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 2, characterized in that: The diene derivatives include N,N'-(4,4'-methylenediphenyl)bismaleimide.

5. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 2, characterized in that: The hydrazide compound includes nicotinic acid hydrazide or benzoyl hydrazide.

6. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 2, characterized in that: The aliphatic diisocyanate includes hexamethylene diisocyanate, isophorone diisocyanate or dicyclohexylmethane-4,4'-diisocyanate.

7. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 2, characterized in that: The enol blocking agent includes dihydromyrcenol.

8. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 2, characterized in that: The mass ratio of the mixed emulsion, the organic tin catalyst and the enol capping agent is 1:0.0005-0.001:0.4-0.

5.

9. A method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 2, characterized in that: The keto compound containing a carbon-carbon double bond includes N,N'-methylenebisacrylamide or diacetoneacrylamide.

10. The method for preparing a heat-sealing cover tape capable of preventing self-adhesion according to claim 1, characterized in that: The preparation method of the pretreated polyethylene film comprises the following steps: The polyethylene film is treated under irradiation conditions of 100 Gy / h to 110 Gy / h radiation dose rate and 50 kGy to 90 kGy radiation dose to obtain the pretreated polyethylene film.

Citation Information

Patent Citations

  • Anti-adhesion and anti-static heat-seal coating and cover tape

    CN112500753A

  • Heat-sealing cover tape with multi-layer structure and preparation method thereof

    CN113426643A

Cited By

  • Anti-self-adhesion and antistatic heat-sealing cover tape and preparation method thereof

    CN120944478A